Confirmatory Population Pharmacokinetic Analysis for Sirukumab, a Human Monoclonal Antibody Targeting Interleukin‐6, in Patients With Moderately to Severely Active Rheumatoid Arthritis. (26th March 2018) - Xu, Yan; Hu, Chuanpu; Zhuang, Yanli; Hsu, Benjamin; Xu, Zhenhua; Zhou, Honghui
Abstract: The population pharmacokinetics of sirukumab, a human immunoglobulin G1κ monoclonal antibody against interleukin‐6, were characterized in patients with moderately to severely active rheumatoid arthritis in 4 phase 3 studies (SIRROUND‐D, ‐T, ‐H, and ‐M). A total of 17 034 serum concentrations were analyzed from 1991 rheumatoid arthritis patients who received subcutaneous administration of sirukumab 50 mg every 4 weeks or 100 mg every 2 weeks. A stepwise confirmatory population PK analysis was conducted to accommodate the staged data release and the sparse sampling nature of phase 3 studies and to assess the potential covariate influences in an unbiased and timely manner. The base model, that is, a 1‐compartment linear model with first‐order absorption and first‐order elimination, was prespecified based on prior information from a phase 2 study along with information about phase 3 study design. The covariate model was also prespecified based on pharmacological/physiological relevance and sample size. After the primary covariate analysis, a simplified model was produced by removing covariates with effect sizes <10%. The estimated apparent clearance (CL/F) and volume of distribution were 0.641 L/day and 16.1 L, respectively, at standard body weights of 70 kg. The terminal elimination half‐life was approximately 17.4 days. Sirukumab CL/F and volume of distribution increased with body weight, and CL/F was higher in patients with diabetic comorbidity. Simulations suggest that the effects of diabetic comorbidity and weight on sirukumab exposure were additive. To fully understand the clinical relevance including potential dose adjustment, current covariate findings need to be evaluated concurrently with the efficacy and safety data.